1940
DOI: 10.1172/jci101160
|View full text |Cite
|
Sign up to set email alerts
|

On the Exacerbation in Chronic Glomerulonephritis

Abstract: In order to gain a better understanding of the r6le of infection in chronic glomerulonephritis, a study of the exacerbations in this disease was undertaken. Sixty-eight patients with chronic glomerulonephritis were observed closely for periods of from 1 to 8 years. An analysis was made of the incidence of the exacerbations in this group, the presence and nature of the infection preceding each exacerbation, the latent period between the infection and the signs of increased renal inflammation and, finally, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

1942
1942
1984
1984

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Four instances of exacerbation in chronic glomerulonephritis were observed, one of which occurred in patient 8, whose initial attack of acute glomerulonephritis was also studied. The criterion accepted for the diagnosis of exacerbation in chronic glomerulonephritis was "an abrupt and marked increase in the degree of hematuria" (8). Foreshortening of the latent period between infection and onset of symptoms characteristic of the exacerbation (8,9) was noted in two of these patients.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Four instances of exacerbation in chronic glomerulonephritis were observed, one of which occurred in patient 8, whose initial attack of acute glomerulonephritis was also studied. The criterion accepted for the diagnosis of exacerbation in chronic glomerulonephritis was "an abrupt and marked increase in the degree of hematuria" (8). Foreshortening of the latent period between infection and onset of symptoms characteristic of the exacerbation (8,9) was noted in two of these patients.…”
Section: Methodsmentioning
confidence: 98%
“…A greater fraction than normal of filtered potassium and inorganic phosphate appear in the urine in the majority of patients. 8. Ammonia excretion is greater than normal during the early phases of acute glomerulonephritis but subsequently falls below the usual normal range.…”
mentioning
confidence: 95%
“…Further, the latent period between precipitating infection and the onset of symptoms or signs of acute nephritis exceeded 5 days in 29 of the 33 patients in whom the latent period could be estimated. Latent periods of 5 to 28 days are characteristic of the initial attack of acute poststreptoccocal glomerulonephritis, in contrast to 1 to 5 days of the exacerbation in chronic glomerulonephritis (26).…”
Section: Methodsmentioning
confidence: 99%
“…The present study is based on this material, with the addition of 5 exacerbations that have been observed since the completion of the earlier study. Two of these exacerbations occurred in a patient (Case XI, PA) previously reported (1), while the other 3 were observed in 2 of 13 new cases studied.…”
mentioning
confidence: 80%
“…In a previous study (1), an exacerbation in chronic glomerulonephritis was defined arbitrarily as an abrupt and marked increase in the degree of hematuria. It was pointed out that slight variations in the urinary output of erythrocytes perhaps do not signify the presence of an exacerbation.…”
mentioning
confidence: 99%